PENGARUH FOSFAT (TSP 36) TERHADAP PERTUMBUHAN RUMPUT LAUT - Y Yunus; Indah Wahyuni Abida; Firman Farid Muhsoni (Department of Marine Sciences, Trunojoyo University of Madura, Indonesia, 2010)
During its growing and development, sea-weed needs nutrient from sea water, instead of light quality and also sufﬁcient organic matter such as nitrate and phosphat. Phosphat is one of the essential organic matters for metabolism of plants cell and also sea-weed growing. This research is aimed to know the effect of phosphat (TSP 35) addition toward the sea-weed growing Eucheuma cottonii, which was done on Desember 2009 in Laboratorium of marine science, agriculture faculty, Trunojoyo university. The design used for this research is complete random sampling with 5 treatments within phoslat (TSP 36) concentration PO = control, PI =0,1, P2 = 0,2, P3 = 0,4 and P4 = 0,8 ppm with 3 repetitions. The result shows that sea-weed growing is affected by phosphat addition. Treatment PI is signiﬁcantly different with treatment P3 and P4, and not signiﬁcantly different with treatment PO don P2. The most appropriate sea-weed growing condition is gained from treatment P4 with value 55,33 gram, with daily-growing average value 0,53%.Kate Kunci: Phosfat (TSP 36), Euchema cottonii, growing.